Bio-valorization potential of banana peels (musa sapientum): an overview - Jamal, Parveen; Saheed, Olorunnisola Kola; Alam, Md Zahangir (Knowledgia Review, Malaysia, 2012)
Recent breakthrough in industrial biotechnology offer important economic opportunities for the utilization of agro-industrial residues such as Banana Peels (BP). BP as a complex biological material is an important by-product of several cottage and major hospitality industries. Chemically, it contains cellulose, hemicelluloses, lignin and simple sugars. Due to its availability and value, it is capable as an ideal substrate for microbial process for production of valued-added products. Several efforts have been made to produce protein enriched animal ration, industrial enzymes, citric acid and other industrially viable products. Pre-treatment operations have resulted in improved substrate utilization by microorganisms. Solid State Fermentation (SSF) and submerged state fermentation (SmF) are two promising techniques majorly employed for bioconversion of BP for its value addition. The article reviews recent developments in process and products developed for valorizing BP through biotechnological approach. Information on most recent applications and developments are carefully documented.